Crosslinked glutinous rice starch filled polyvinyl alcohol films. Issue 4 (26th March 2019) - Yeng, Chan Ming; Chun, Koay Seong
Abstract : The influence of glutinous rice starch (GRS) content and sodium hexametaphosphate (SHMP) in polyvinyl alcohol (PVOH) films were studied. The increase of GRS content (0–40 wt%) reduced the tensile strength (from 14.3 to 4.3 MPa) and elongation at break (from 183 to 52.5) of PVOH/GRS films. Nevertheless, the modulus of elasticity of PVOH/GRS films increased with GRS content, from 20.3 to 132.83 MPa. SHMP was used as a crosslinking agent, which improved more than 30% of tensile strength and modulus of elasticity of PVOH/GRS films. However, the elongation at break reduced after crosslinking process of the films. The crosslinked film showed better interaction between GRS and PVOH, as demonstrated by scanning electron microscopy. Conversely, the crosslinked films exhibited a lower swelling degree, but a higher gel content compared to uncrosslinked films. J. VINYL ADDIT. TECHNOL., 25:359–365, 2019. © 2019 Society of Plastics Engineers